Security performance analysis for power domain NOMA employing in cognitive radio networks - Thi-Anh Hoang; Chi-Bao Le; Dinh-Thuan Do (Bulletin of Electrical Engineering and Informatics, 2020)
The power domain non-orthogonal multiple access (NOMA) technique introduces one of the fundamental characteristics and it exhibits the possibility of users to decode the messages of the other paired users on the same resources. In cognitive radio inspired NOMA (CR-NOMA), the base station (BS) has to serve untrusted users or users with different security clearance. This phenomenon raises a security threat particularly in such CR-NOMA. This paper develops a tractable analysis framework to evaluate the security performance of cooperative non-orthogonal multiple access (NOMA) in cognitive networks, where relay is able to serve two far NOMA users in the presence of external eavesdropper. In particular, we study the secrecy outage probability in a two-user NOMA system. This situation happens in practical the BS is pairing a legitimate user with another untrusted user. Main reason is that the non-uniform distribution in terms of trusted and untrusted users in the cell. By performing numerical results demonstrate the performance improvements of the proposed NOMA scheme in comparison to that of several situations in terms of different parameters. Furthermore, the security performance of NOMA is shown to verify the derived expressions.